Analysis of Mathematics Learning in the Implementation of The Merdeka Curriculum at Muhammadiyah Palangka Raya Integrated Islamic Elementary School - Dedy Setyawan; Amelia Dwi Astuti; Nurun Ni'mah (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Background: The implementation of the Merdeka curriculum in schools, especially at muhammadiyah palangka raya integrated islamic elementary school has become a concern. This is because the results of initial observations found that teacher and student activities during learning could not support student learning outcomes, especially in Mathematics learning. Thus, it is important to analyze mathematics learning in implementing the Merdeka curriculum at muhammadiyah palangka raya integrated islamic elementary school. Aim: Aim of this research is to describe the analysis of mathematics learning in implementing the independent curriculum at SD IT Muhammadiyah Palangka Raya. Method: This type of research is a type of qualitative research where the data that is found will be described according to the research focus. Data collection techniques in this research are observation, interviews and documentation. The data that has been collected is then analyzed and reduced using data simplification and retrieval of supporting data in this research so that the conclusions drawn can be justified. Results and Dıscussion: The results of the research show that mathematics learning in implementing the independent curriculum has been carried out well at muhammadiyah palangka raya integrated islamic elementary school. This can be seen from the preparation and implementation stages which have gone well. Conclusion: Muhammadiyah Palangka Raya integrated Islamic Elementary School has implemented mathematics education well as part of its Merdeka curriculum. This is evident from the proficient execution of the majority of preparation and learning components.